The Association Between Perceived Care From Family, School Staff, and Other Social Agents and an Adolescent’s Presentation of Empathy, Trait Resilience, and Psychological Strengths - Leung, Tiffany SY; Rawana, Edward; Klein, Rupert (Alberta Journal of Educational Research, 2020)
The abilities to experience and understand another person’s feelings (empathy), to successfully cope with stress (resilience), and to harness personal skills (psychological strengths) are dynamic qualities that may be associated to an adolescent’s perception of care from others (i.e., family, friends, school staff, and significant others). Although the association of these different social sources have been studied independently, it has yet to be elucidated which of these sources is most highly associated to the presentation of these three qualities. For this study, high school students from a northern community completed a series of online questionnaires. A series of hierarchical regressions showed each source of care accounted for unique variance in the presentation of resilience and strengths, with perceived care from school staff and family accounting for the greatest variance, emphasizing the equal importance of examining the school and home environment. Further research is needed to understand how teachers and the school culture are associated with personal growth. Keywords: adolescent growth, resilience, psychological strengths, positive psychology, social support Les capacités de ressentir et de comprendre les sentiments d’autrui (l’empathie), de bien gérer le stress (la résilience) et d’exploiter ses compétences personnelles (forces psychologiques) sont des qualités dynamiques qui peuvent être associées à la perception qu’ont les adolescents des soins dispensés par les autres (c.-à-d., la famille, les amis, le personnel de l’école et l’être cher). Si l’association de ces différentes sources sociales a été étudiée indépendamment pour chacune d’elles, il reste à comprendre laquelle est la plus fortement liée aux trois qualités décrites ci-haut. Dans le cadre de cette étude, des élèves du secondaire provenant d’une communauté du nord ont complété une série de questionnaires en ligne. Une série de régressions hiérarchiques a démontré que chaque source de soins expliquait une variance unique dans la présentation de la résilience et des forces. Les soins perçus de la part du personnel de l’école et de la famille représentent la plus grande variance, ce qui souligne l’importance de se pencher tant sur le milieu scolaire que le milieu familial. Il faudrait mener des recherches plus poussées pour comprendre dans quelle mesure les enseignants et la culture scolaire sont associés à l’épanouissement personnel. Mots clés: croissance des adolescents; résilience; forces psychologiques; psychologie positive; soutien social